Concentric Needle Jitter in 97 Myasthenia Gravis Patients - Kouyoumdjian, João Aris; Paiva, Gabriel Pina; Stålberg, Erik (Frontiers in Neurology, 2020)
Objectives: To estimate the jitter parameters (single-fiber electromyography) in myasthenia gravis patients mostly by electrical activation in Frontalis, Orbicularis Oculi, and Extensor Digitorum muscles using a concentric needle electrode. Methods: Between 2009 and 2019, a total of 97 myasthenia gravis patients, 52 male, and mean age 54 years were included. Results: Any abnormal jitter parameter in individual muscles was 90.5% (Frontalis), 88.5% (Orbicularis Oculi), and 86.6% (Extensor Digitorum). Any jitter parameter combining Orbicularis Oculi and Frontalis muscle was abnormal in 100% for the ocular, and in 92.9% for the generalized myasthenia gravis. The most abnormal muscle was Orbicularis Oculi for the generalized, and Frontalis for the ocular myasthenia gravis. The decrement was abnormal in 78.4%, 85.9% for the generalized, and 25% for the ocular myasthenia gravis. The mean jitter ranged from 14.2 to 86 µs (mean 33.3 µs) for the ocular myasthenia gravis and from 14.4 to 220.4 µs (mean 66.3 µs) for the generalized myasthenia gravis. The antibody titers tested positive in 86.6%, 91.8% for the generalized, and 50% for the ocular myasthenia gravis. Thymectomy was done in 48.5%, thymoma was found in 19.6%, and myasthenic crisis occurred by 21.6%. Conclusion: The jitter parameters achieved a 100% abnormality in ocular myasthenia gravis if both the Orbicularis Oculi and Frontalis muscles were tested. There was a high jitter abnormality in generalized myasthenia gravis cases with one muscle tested, with about a 2% increase in sensitivity when a second is added. Concentric needle electrode jitter had high sensitivity similar to the single fiber electrode (93.8%), followed by antibody titers (86.6%), and abnormal decrement (78.4%).